Speechlessness, anxiety, and confusion in a teacher education student group - Räihä, P.; Moilanen, P.; Dobozy, Eva; Saukkonen, S. (2017)
The aim of the study was to explore the tensions, as experienced by student teachers, in a teacher education program that is based on psychodynamic theory. Previous research shows that students have had orientation problems in innovative university studies because it involves students having to take steps toward their discomfort zone. It was therefore considered important to study the mismatch or match of the training model and student experiences. The data were gathered through student interviews. The data analysis utilized a case study methodology and proceeded from thematic network analysis toward a deeper interpretation of the data. The analysis shows students struggle to understand the meaning and practices of psychodynamic-oriented pedagogy. The analysis also shows that students were unable and unwilling to share their learning experiences with students outside the new program. This can be understood as a tension between different conceptual understandings of learning.